Alterations of the Human Gut Microbiota in Intrahepatic Cholestasis of Pregnancy - Zhan, Qitao; Qi, Xuchen; Weng, Ruopeng; Xi, Fangfang; Chen, Yuan; Wang, Yayun; Hu, Wen; Zhao, Baihui; Luo, Qiong (Frontiers in Cellular and Infection Microbiology, 2021)
Background and Aims Women with severe intrahepatic cholestasis of pregnancy (ICP) are at higher risks of fetal complications and without effective treatments. Changes in gut microbiota in pregnancy were found to be related to the altered intestinal bile acid composition, so we aimed to explore the alterations of microbiota in the gut of ICP patients. Methods A total of 90 women were recruited, including 45 ICP patients and 45 healthy controls. The gut microbiota communities of ICP group were compared to control group through 16S ribosomal RNA gene sequencing. The results were then confirmed by real-time polymerase chain reaction (PCR) and generalized linear model (GLM). Furthermore, we analyzed the relationships between microbiota and the severity of ICP. Results A total of seven genera and nine taxa with differential abundances between the ICP patients and the controls were identified. All of the seven genera were verified through real-time PCR, and three key genera Parabacteroides, Flavonifractor, and Megamonas were confirmed by using the GLM model. Further analysis found that the genera Escherichia_Shigella, Olsenella, and Turicibacter were enriched in the severe ICP group, the microbial gene function related to biosynthesis of unsaturated fatty acids and propanoate metabolism were also increased in them. Conclusions Overall, our study was the first in Asia to demonstrate an association between gut microbiota and ICP. Our findings would contribute to a better understanding of the occurrence of ICP.